Follicular Dendritic Cell Sarcoma of the Larynx: Apropos a Rare Case with Review of the Literature - Ayushi SAHAY; Munita BAL; Asawari PATIL; Shubhada KANE; Prathamesh PAI (Federation of Turkish Pathology Societies, 2019)
Extranodal follicular dendritic cell sarcomas are extremely rare neoplasms included under the hematolymphoid and dendritic group of neoplasms. Histologically, fascicular, whorled spindle cells with sprinkled lymphocytes are typical; however higher grade epithelioid morphology seen in a subset makes diagnosis of follicular dendritic cell sarcoma challenging. Rarity of occurrence, a wide histologic spectrum and a long list of differential diagnostic entities render follicular dendritic cell sarcoma an under-recognized entity susceptible to diagnostic pitfalls. Application of a judicious panel of immunohistochemical markers is imperative to avoid errors in diagnosis and patient management. We report here an extremely rare case of follicular dendritic cell sarcoma of the larynx- a hitherto unreported site.